Clinical use of the Oncotype DX genomic test to guide treatment decisions for patients with invasive breast cancer - McVeigh, Terri P (Breast Cancer (Dove Med Press), 2017)
Implementation of the Oncotype DX assay has led to a change in the manner in which chemotherapy is utilized in patients with early stage, estrogen receptor (ER)-positive, node-negative breast cancer; ensuring that patients at highest risk of recurrence are prescribed systemic treatment, while at the same time sparing low-risk patients potential adverse events from therapy unlikely to influence their survival. This test generates a recurrence score between 0 and 100, which correlates with probability of distant disease recurrence. Patients with low-risk recurrence scores (0–17) are unlikely to derive significant survival benefit with adjuvant chemotherapy and hormonal agents derived from using adjuvant hormonal therapy only. Conversely, adjuvant chemotherapy has been shown to significantly improve survival in patients with high-risk recurrence scores (≥31). Trials are ongoing to determine how best to manage patients with recurrence scores in the intermediate range. This review outlines the introduction and impact of Oncotype DX testing on practice; ongoing clinical trials investigating its utility; and challenging clinical scenarios where the absolute recurrence score may require careful interpretation. We also performed a bibliometric analysis of publications on the topics of breast cancer and Oncotype DX as a surrogate marker of acceptability and incorporation of the assay into the management of patients with breast cancer.